Flexible freestanding MoS2-based composite paper for energy conversion and storage - Zoller, Florian; Luxa, Jan; Bein, Thomas; Fattakhova-Rohlfing, Dina; Bouša, Daniel; Sofer, Zdeněk (Beilstein Journal of Nanotechnology, 2019)
The construction of flexible electrochemical devices for energy storage and generation is of utmost importance in modern society. In this article, we report on the synthesis of flexible MoS2-based composite paper by high-energy shear force milling and simple vacuum filtration. This composite material combines high flexibility, mechanical strength and good chemical stability. Chronopotentiometric charge–discharge measurements were used to determine the capacitance of our paper material. The highest capacitance achieved was 33 mF·cm−2 at a current density of 1 mA·cm−2, demonstrating potential application in supercapacitors. We further used the material as a cathode for the hydrogen evolution reaction (HER) with an onset potential of approximately −0.2 V vs RHE. The onset potential was even lower (approximately −0.1 V vs RHE) after treatment with n-butyllithium, suggesting the introduction of new active sites. Finally, a potential use in lithium ion batteries (LIB) was examined. Our material can be used directly without any binder, additive carbon or copper current collector and delivers specific capacity of 740 mA·h·g−1 at a current density of 0.1 A·g−1. After 40 cycles at this current density the material still reached a capacity retention of 91%. Our findings show that this composite material could find application in electrochemical energy storage and generation devices where high flexibility and mechanical strength are desired.
Keywords: flexible composites; hydrogen evolution reaction (HER); lithium ion batteries (LIBs); molybdenum disulfide; nanoarchitectonics; supercapacitors